Pemanfaatan Teknologi Media Pembelajaran di Masa Pandemi Covid-19 - Riasatul Habibah; Unik Hanifah Salsabila; Windi Mega Lestari; Oqy Andaresta; Diah Yulianingsih (Trapsila: Jurnal Pendidikan Dasar, 2020)
In everyday life we are used to dealing with technology, but it is different today. Since the covid-19 virus came to the world, especially the Indonesian state, Indonesian education has been carried out differently. During this pandemic, education was carried out by utilizing learning platforms that actually existed but were rarely used, but for now of course it is a new thing for some education circles because they are not familiar with technology in education. There are so many platforms that can be used for online learning that can be used by all educational institutions including children in elementary schools, namely there is a google classroom which is a form of e-learning that uses WebCT, YouTube, WAG, Edmodo, Zoom, Googlemeet and there are many other supporting applications. This study aims to determine the use of online learning technology during the Covid-19 pandemic using the Google classroom, YouTube, WAG, Edmodo, Zoom, and Googlemeet platforms. And the results of research using the interview method, literature and literature study show that technology has many roles and benefits in the world of education, especially when learning in the midst of the Covid-19 pandemic. By conducting interviews with teachers and students, it can be concluded that the learning media technology that is mostly used by elementary schools is WAG and also google classroom.Keywords: covid-19, platform google classroom, online learning, WAG.